A Comprehensive Analysis of the Current Status and Unmet Needs in Kidney Transplantation in Southeast Asia - Chan-on, Chitranon; Sarwal, Minnie M. (Frontiers in Medicine, 2017)
To address the unmet needs in the face of a growing demand for end stage renal failure management and kidney transplantation in Asia, we have conducted a critical analysis of published literature and national registries to evaluate clinical outcomes and the rates of organ donation in South-East Asia and the challenges facing these regions with regards to regulation, choice of donor source and funding. Based on the available data, suggestions are proposed for an advancement of rates of organ donation and access, with emphasis on improved regulation and public education.